2013
DOI: 10.1097/igc.0b013e31827da23f
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of E-Cadherin and Integrin β-1 in Trophoblasts Is Associated With Malignant Gestational Trophoblastic Diseases

Abstract: Aberrant expression of E-cadherin and integrin β-1 is closely related to malignant transformation and hydatidiform mole development. Changes in the expression of E-cadherin and integrin β-1 are informative and may improve the early diagnosis of malignant/invasive moles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
1
4
1
Order By: Relevance
“…Low expression of E‐cadherin is correlated with tumor invasion and progression . Although high E‐cadherin expression was observed in normal placental cytotrophoblasts, its expression significantly decreased from normal placenta to malignant iHMs . Surprisingly, high E‐cadherin expression in normal placenta and different stages of HMs was observed in this study, which is contradictory to most previous studies .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Low expression of E‐cadherin is correlated with tumor invasion and progression . Although high E‐cadherin expression was observed in normal placental cytotrophoblasts, its expression significantly decreased from normal placenta to malignant iHMs . Surprisingly, high E‐cadherin expression in normal placenta and different stages of HMs was observed in this study, which is contradictory to most previous studies .…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study reported that E-cadherin expression in trophoblastic villus was gradually decreased from normal placenta to malignant HMs [13]. In this study, we observed that E-cadherin expression was positive in cytotrophoblasts and extravillous trophoblast of normal placenta ( Figure 1A), and a similar expression pattern was found in pHMs and cHMs ( Figures 1B and 1C).…”
Section: E-cadherin Expression In Normal Placenta and Different Stagesupporting
confidence: 80%
See 2 more Smart Citations
“…Previous studies have reported that the expression of EMT markers, including Zeb1, Zeb2, Twist family BHLH transcription factor and Snail family transcriptional repressor 1 in the outer cell layer of trophoblasts is increased at 22 days gestation (12). Therefore, it may be speculated that Zeb1 is involved in regulation of trophoblastic invasion (13). However, to the best of our knowledge, research into human chorionic villi is limited.…”
Section: Introductionmentioning
confidence: 99%